Optimum Simplex Lattice Designs of Low Order Multiresponse Surface Model by D-Optimum Criterion - Ruslan Ruslan; Susanti Linuwih; Purhadi Purhadi; Sony S (Jurnal ILMU DASAR, 2010)
Simplex lattice design is a part of mixture designs has patterns simplex {q, m} where q is number of factors andm is degree of polynomial. If entangling a number of the response variables which measured from a number offactors called the multiresponse surface model, hence to obtain get the matrix designs of optimum mixture atmultiresponse surface model will be used by the optimum-D criterion. In this research, we studied abouttheoretical approach to get optimum simplex lattice design of low order multiresponse surface model byoptimum-D criterion. We assumed that design points have similar weighted values.